Study of radiation hardness of HfO2-based resistive switching memory at nanoscale by conductive atomic force microscopy. Issue 11 (November 2015) - Lin, Shih-Hung; Wu, You-Lin; Hwang, Yu-Huei; Lin, Jing-Jenn
Highlights: We investigated the resistive switching behaviors of RRAM cell with extremely small area before and after γ-ray irradiation. Forming voltage, set voltage, resistance of high- and low-resistance states are all radiation dose-dependent. A comprehensive model was proposed to explain the changes in post-irradiated resistive switching behaviors. Abstract: A resistive switching random access memory (RRAM) with an HfO2 /Ti structure grown on a molybdenum (MO) substrate was fabricated, and a gold (Au) conductive atomic force microscopy (CAFM) tip was used as the top electrode such that the cell area of the resulting RRAM device is as small as 3 × 10 −12  cm 2 . The pre- and post-irradiated resistive switching behaviors of the RRAM device with various HfO2 layer thicknesses were investigated after being subjected to Co 60 γ-ray irradiation with different radiation doses. It is found that the forming voltage ( V forming ), set voltage ( V set ), resistance of high resistance state (RHRS) and resistance of low resistance state (RLRS) of the RRAM device are all radiation dose-dependent. The V forming, V set, RHRS and RLRS all decrease as the radiation dose increases due to increasing radiation-induced oxygen vacancies or defects inside the HfO2 layer. Our experimental results indicate that the HfO2 -based RRAM cell with an extremely small cell area is not actually radiation hard since the operating voltage will change with V forming and V set after irradiation.